Ecological policy in oil-gas complexes, HSE MS implementation in oil and gas company; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Kochetkova O. P. Olga Petrovna; Glyzina T. S. Tatiana Svyatoslavovna; Vazim A. A. Andrey Aleksandrovich; Tugutova S. S. (Geoecology and Environmental Protection, 2016)
Title screen